Lagochilus species and diterpenes isolated from them. ( Chiqarishga berilgan) (Texas Journal of Agriculture and Biological Sciences, 2022)
Lagohilus is a very common and promising medicinal plant. All over the world, extracting substances with high biological activity from the composition of plants and creating new medicines based on them is developing rapidly. Natural compounds isolated from the composition of plants have high biological activity, and their use in medical practice and folk economy occupies a special place. The main active ingredient of the Lagoxilus plant is the diterpenoid lagoxilin, which is a four-atom alcohol. Therefore, most plants belonging to the genus Lagochilus have hemostatic properties.